تفعيل العناقيد الصناعية كآلية لاستدامة المشروعات الصغيرة والمتوسطة: دراسة ميدانية علي صناعة الأثاث بمحافظة دمياط - رفاعي، عبير محمد عباس محمد (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2020)
يهدف البحث الحالي إلى التعرف على آليات تفعيل العناقيد الصناعية والتي تسهم في استدامة المشروعات الصغيرة والمتوسطة بصناعة الأثاث بمحافظة دمياط. وتوصل البحث إلى عدد من النتائج أهمها: تدهور صناعة الأثاث بدمياط، ووجود معوقات تواجه صناعة الأثاث، كما ظهر اتجاه إيجابي لدى العينة نحو أهمية تفعيل العنقود الصناعي كآلية لاستدامة المشروعات الصغيرة والمتوسطة بصناعة الأثاث. أما عن آليات تفعيل عنقود صناعة الأثاث فتوصلت الدراسة إلى ضعف بعدي المسئولية الاجتماعية للدولة والقدرة التكنولوجية والمعرفية.
The current research aims at identifying mechanisms for activating industrial clusters as a strategy that helps in achieving sustainability for small and medium enterprises in furniture industry in Damietta Governorate. The research reached a number of results, the most important of which are: the deterioration of the furniture industry in Damietta, and the existence of obstacles facing furniture industry. A positive trend has appeared in the research sample towards the importance of activating the industrial cluster as a strategy of sustainability for small and medium projects in furniture industry. As for the mechanisms for activating furniture industry clusters, the study has proved the weakness of both dimensions: the social responsibility of the State, and the technological and knowledge capacity.
Keywords: السياسة الإقتصادية -- الصناعات الصغيرة -- صناعة الأثات -- العناقيد الصناعية -- محافظة دمياط